PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA - Wiwi Pratiwi Sumardi; Bellona Mardhatillah Sabillah; Muh. Khaedar; Jusmawati Jusmawati (Kelola: Journal of Islamic Education Management, 2022)
This study aims to determine the influence of the school environment on student motivation at inpres Borong Jambu II Elementary School in Makassar. The type of research used is ex post facto with a quantitative approach. The population used was class 5A and 5B of the Inpres Borong Jambu II Elementary School in Makassar, amounting to 54 people. The sample of this study was 5b class student consisting of 26 students, and the instrument used were questionnaires and documentation with a siple random sampling technique. The study results using descriptive statistical analysis, the average vaule of the school environment is 51.85 in the very high category, and learning motivation with a total of 44.58 is in the very motivated category. Prerequisite analysis of school environment normality test results and learning motivation 0,200>0,05 (normal distribution), homogeneity test results 0,658>0,05 (homogeneous). The result of the linearity test is 0,582>0,05. Based on these results, there is a linear relationship between the school environment and learning motivation. The results of the hypothesis test showed a sig value of 0,000 with the criteria of sig (0,000) <α (0,05).The conclusion in this study is that there is an influence of the school environment on student motivation of class V Inpres Borong Jambu II Elementary School in Makassar.